2021
DOI: 10.9743/jeo.2021.18.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Versus Video Discussion to Promote a Sense of Community: An International Mixed-Methods Study

Abstract: Creating an engaging online course where students feel part of an online community can be challenging even for the most experienced online educator. Online discussions are a common tool used to connect students in online courses, but it is often limited to text-based posts. This international research study compared the use of text-based versus video-based discussions in online courses to ascertain students’ perceptions of social presence. A mixed-methods design using a modified Social Presence, Likert-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Most studies have suggested that online discussion environments improve students' learning achievement, engagement, social presence, and HOTS (Aderibigbe, 2021; Murphy et al, 2021). These environments have been utilised to support OL or blended formats such as FC by encouraging a more in‐depth analysis and critical reflection.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have suggested that online discussion environments improve students' learning achievement, engagement, social presence, and HOTS (Aderibigbe, 2021; Murphy et al, 2021). These environments have been utilised to support OL or blended formats such as FC by encouraging a more in‐depth analysis and critical reflection.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A major concern is the lack of interaction and engagement, especially during the pre‐class activities of FC (Sun & Lin, 2022). To minimise these issues, different discussion methodologies are mainly used in OL (Murphy et al, 2021): text‐based (text responses) and video‐based (video responses) discussions. In addition, there are discussion tools that include several media formats such as voice and pictures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%